Social isolation, loneliness, and subjective wellbeing among Chinese older adults during the COVID-19 pandemic - Hao, Haijun; Du, Mengqi; Yue, Junyue (Frontiers in Public Health, 2024)
The COVID-19 pandemic has brought unprecedented challenges to the wellbeing of the older adults worldwide. Both social isolation and loneliness are associated with decreased subjective wellbeing, but it is uncertain whether their effects are independent or if loneliness represents the affective pathway through which social isolation impairs subjective wellbeing. We therefore assessed the extent to which the association between social isolation and subjective wellbeing is mediated by loneliness. We utilized data from the 2020 China Family Panel Studies (CFPS) and focused on a sample of 3,821 individuals aged 60 and above as the participants for our study. The results revealed a significant negative association between social isolation and subjective wellbeing among the older adults during the COVID-19 pandemic. Furthermore, loneliness was found to mediate this relationship, indicating that social isolation led to increased feelings of loneliness, which in turn negatively impacted subjective wellbeing. These findings highlight the detrimental effects of social isolation and loneliness on the wellbeing of the older adults in China during the pandemic. The implications of these results emphasize the need for interventions and support systems that address social isolation and loneliness among the older adults, promoting their wellbeing and overall mental health during challenging times such as the COVID-19 pandemic.